Pattern of malocclusion in patients seeking orthodontic treatment at Dhaka Dental College and Hospital (Bangladesh Journal of Orthodontics and Dentofacial Orthopedics, 2015)
Aims: To evaluate the pattern and distribution of malocclusion in patients seeking orthodontic treatment in Dhaka Dental College Hospital.Material and Methods: Total of 400 patients were included in the study with a mean age of 19.10 years. A standard format was prepared to record the data. Ages, sex and Class I, II and III malocclusions were tabulated to cheek for any relationship.Results: The prevalence of molar class I, II, III and both (I &II) malocclusion were 61.53%, 22.56%, 8.2%, and 7.17%, respectively. The prevalence of incisors class I, class II division 1,classII division 2 and class III malocclusions were 36.92%, 39.74%, 2.56% and 14.87%. out of 400 cases the distribution of various occlusal abnormality were spacing 40%, crowding 46.92%, cross bite 23.07%, open bite 8.46%, impaction 6.41%, rotation 20%, median diastema 13.58%, absent  teeth 7.69%, mesiodense 2.51% and cleft lip and palate was 1.28%. Most prevalence  age group seeking orthodontics treatment was 16 to 20 years with female to male ratio 2.45 :1.Conclusion: class I malocclusion was the most prevalent followed by class II malocclusion and class III malocclusion showed least prevalence.Ban J Orthod & Dentofac Orthop, April 2013; Vol-3, No.2